International Students' Social Outcomes, Educational Status, and Country of High School Graduation. (November 2019) - Brunsting, Nelson C.; Mischinski, Megan; Wu, Wenjin; Tevis, Tenisha; Takeuchi, Risa; He, Yueying; Zheng, Yihan; Coverdell, Travis L.
Despite the increase in methodological sophistication and complexity of models being tested for international student adjustment to universities in the United States (U.S.), researchers often do not test or control for salient demographic differences between students, including their educational status (i.e., graduate or undergraduate) and country in which they graduated high school. The current study was designed to examine whether demographic variables are associated with a range of social outcomes. Participants ( N = 245) from 23 U.S. colleges and universities completed a survey in Fall 2017. Undergraduate students reported having a higher number of close friends at their institution than did graduate students; however, they also reported a lower sense of belonging than did graduate students. Students who graduated from high school in the United States reported less social support from international students at university. Implications for students and for future research are provided.